(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2013)
This paper presents the implementation and comparison of algorithms for support vector machines “SVM” and AdaBoost in the classification of public and private vehicles using segmented images of video sequences taken in Bogotá city. Using as tools the OpenCV libraries implemented in C. The algorithms performances are remarkable and therefore its use could have a positive impact in the reduction of traffic problems.